Language and Logics - Gregory, Howard (Edinburgh University Press, 2015)
Chapter 1 Meaning and Logic -- PART I The Classical Picture -- Chapter 2 Truth Table Logic -- Chapter 3 Predicates -- Chapter 4 Quantifiers -- Chapter 5 Functions: The Lambda Calculus -- PART II Modality -- Chapter 6 Possibility and Necessity -- chapter 7 Worlds and Individuals -- PART III Negation and Partiality -- Chapter 8 Many Valued Logics -- Chapter 9 Situations and Information -- Chapter 10 Intuitionism and Constructive Proof -- PART IV Substructural Logics and Categorial Grammar -- Chapter 11 Relevance, Resources and Order -- Chapter 12 Grammar as Logic -- Chapter 13 Combinators; Includes bibliographical references (pages 302-309) and index